COVID-19 Vaccine Development to Vaccination - Pandey, Ashok; Belbase, Pradeep; Parajuli, Ayuska (Journal of Nepal Health Research Council, 2021)
In the race for a safe and effective vaccine against Coronavirus disease-19 manufacturer plays a critical role throughout the development, clinical trial, manufacturing, supply, and vaccination phases. For the efficacy of Coronavirus disease-19 vaccine, proper transport, storage, vaccine carrier, adjuvant, dosage form and route of vaccine administration plays a crucial role for immune response. In the context of no more people were willing to pay for a Coronavirus disease-19 vaccine the logistics of manufacturing, storing and distributing the vaccine, and mass vaccination are essential. It is urgent to improve health promotion and reduce the barriers to Coronavirus disease-19 vaccination. Keywords: COVID-19; vaccine development; vaccination